GROWTH AND SURVIVAL OF SPINY LOBSTER, Panulirus homarus JUVENILES FED WITH DIFFERENT FORMULATED FEEDS - Sudewi Sudewi; Bejo Slamet; Nyoman Adiasmara Giri; Haryanti Haryanti; Ibnu Rusdi; Clive Jones; Simon Irvin (BIOTROPIA, 2024)
Article Highlights- Indonesia has remarkable natural resources of spiny lobster Panulirus homarus and an exceptional opportunity to establish the largest lobster aquaculture industry in the world.- However, culturing lobsters still relies on natural feeds (trash fish of fresh fishery by-catch) which are inefficient and environmentally unsustainable.- Developing formulated feed based on locally available ingredients is invaluable for replacing natural feeds to support sustainable lobster culture.- Formulated feed made of local fish meal provided the best growth of juvenile spiny lobster Panulirus homarus compared to imported fish meal. AbstractSeveral studies suggested that good growth performance and survival of lobster juveniles can be achieved by feeding the lobsters with formulated feeds. This study aimed to (1) evaluate the growth and survival of spiny lobster Panulirus homarus juveniles fed with different diets having profiles based on a basal diet formulation and (2) to compare the growth of lobsters fed with an identical formulated feed with variations only in sources of fish meal and dry matter content. The feeding experiment was designed following a completely randomized design (CRD) with five diet treatments and five replicates for each treatment. Five experimental diets were prepared in this experiment, i.e., Diet A (basal diet prepared as moist pellets); Diet B (moist pellets with the same formulation as Diet A, using local fish meal); Diet C (moist pellets with the same formulation as Diet A, using imported fish meal); Diet D (dry pellets with the same formulation as Diet A, using imported fish meal); and Diet E (fresh fish). Juveniles of spiny lobster with an average weight of 3.00±0.07 g were allocated in 25 net cages (60 x 60 x 60 cm) placed in a circular HDPE canvas tank (7.5 m in diameter) at a density of 15 lobsters/cage in a flow-through seawater system. The juveniles were fed with the experimental diets twice/day for 12 weeks. The experiment showed that the best growth was observed in juveniles fed with moist feed containing local fish meal (Diet B) with the final weight reaching 18.74±2.30 g. Moist feed containing imported fish meal (Diet C) resulted in a higher survival rate (46.66%), and the lowest survival rate (13.33%) was obtained from juveniles fed with fresh fish (Diet E).